Porous hollow carbon sphere / sodium ferric sulfate composite material, preparation and application of sodium ion battery

Through the capillary adsorption and sintering process of porous hollow carbon spheres, a porous hollow carbon sphere/sodium ferrosulfate composite material was prepared, solving the problem of state control of the composite state between sodium ferrosulfate and conductive carbon, and significantly improving its electrochemical performance.

CN119764407AActive Publication Date: 2025-04-04NORTHWESTERN POLYTECHNICAL UNIV

Patent Information

Application Number
CN202411969895.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-04
Estimated Expiration
2044-12-30

AI Technical Summary

Technical Problem

The prior art is difficult to effectively control the recombination state of sodium ferrosulfate and conductive carbon, resulting in large particles of sodium ferrosulfate and uneven contact with the conductive carbon, affecting their electrochemical utilization.

Method used

By using the capillary adsorption of porous hollow carbon spheres, the precursor aqueous solution is adsorbed and filled in the pores inside and on the surface of the porous hollow carbon spheres, dried and sintered to form a porous hollow carbon sphere/sodium iron sulfate composite material. This method can effectively control the particle size and composite state of sodium ferric sulfate and promote its contact with the body of conductive carbon.

Benefits of technology

The close contact between sodium ferric sulfate and conductive carbon is achieved, which significantly improves the transmission capacity of sodium ions and electrons, and improves the reversible specific capacity, rate performance and cycle life of the composite material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119764407A_ABST
    Figure CN119764407A_ABST
Patent Text Reader

Abstract

The invention discloses a porous hollow carbon sphere / sodium ferric sulfate composite material, preparation and application of a sodium ion battery, and relates to the technical field of electrode materials. The method comprises the following steps: preparing a mixed solution of sodium sulfate, ferrous sulfate and a reducing agent according to a certain proportion, mixing the mixed solution with porous hollow carbon spheres, and drying to obtain a precursor; and heating the precursor powder to a preset sintering temperature in an inert atmosphere, and keeping the temperature for a period of time to obtain the porous hollow carbon sphere / sodium ferric sulfate composite material. The sodium ferric sulfate composite material in contact with the conductive carbon frame forming body is prepared through the capillary adsorption effect of the porous hollow carbon spheres, confinement anchoring of nanoscale sodium ferric sulfate particles in the porous hollow carbon spheres can be effectively achieved, and rapid transmission of sodium ions and electrons is promoted; the reversible sodium storage capacity, the rate capability and the cycle life are obviously improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of electrode materials, and in particular to a porous hollow carbon sphere / sodium iron sulfate composite material and its preparation and application in sodium ion batteries. Background Art

[0002] In recent years, with the rising demand for large-scale energy storage equipment, the rapid consumption of fossil fuels and the rising price of lithium metal, sodium-ion batteries, which were developed at the same time as lithium-ion batteries, have once again become a hot topic of research. Compared with lithium-ion batteries, sodium-ion batteries have many advantages such as abundant raw materials, low cost, high safety, long life and good stability. Especially in the field of large-scale power grid storage, energy density is no longer the first choice for various battery indicators. The research and application of sodium-ion batteries can effectively alleviate the equipment gap of electric energy storage and promote continuous innovation and resource optimization in the battery technology industry. At the same time, sodium-ion batteries have shown their superior performance in many industries such as new energy vehicles and power tools. However, the development of high-performance cathode materials is still the main problem hindering the further commercial application of sodium-ion batteries.

[0003] There are many types of polyanion positive electrode materials with low cost, adjustable structure, stable framework and three-dimensional sodium ion diffusion channel. At the same time, accompanied by the inductive effect of the anion group, compared with transition metal oxides and Prussian blue analogs, which are also positive electrodes, it has a series of advantages such as excellent stability, high redox potential and extremely small volume change during charge and discharge. Compared with other polyanions, the sulfate anion group has a stronger electronegativity and can produce a stronger inductive effect. Sodium iron sulfate is a representative material with a higher voltage platform. The preparation cost of sodium iron sulfate material is low and the methods are diverse. Its three-dimensional structure provides a stable and fast transmission channel for sodium ions and electrons, which can effectively reduce the volume change of the material during charge and discharge. At the same time, the theoretical specific capacity of sodium iron sulfate material is also high, which means that it has excellent energy density (over 350Wh / kg). The advantages of high voltage platform, large theoretical capacity and low raw material cost prove that sodium iron sulfate has sufficient potential to become a low-cost and high-performance positive electrode material for sodium ion batteries.

[0004] However, sulfate materials are very sensitive to the environment during synthesis and storage. Direct contact with air, high humidity environment, and temperature above 450°C will cause the divalent iron in sodium ferric sulfate to be oxidized or undergo phase change decomposition. Therefore, the environment must be strictly controlled and a reducing agent must be added during its synthesis and storage. Secondly, sodium ferric sulfate itself has poor conductivity and low synthesis temperature, and needs to be compounded with various conductive carbons to ensure excellent electronic and ionic conductivity. Technicians in this field prepare sodium ferric sulfate composite materials by ball milling or spray drying, but fail to better control the composite state of conductive carbon and sodium ferric sulfate. The two often form point-to-surface contact rather than body contact, and the obtained sodium ferric sulfate particles are larger, resulting in poor composite effect with conductive carbon. In summary, large particles of sodium ferric sulfate and its uneven contact with conductive carbon are not conducive to the electrochemical utilization rate at the subsequent battery level.

[0005] Therefore, based on the above problems, it is urgent to invent a method with simple process flow, good safety, capable of making sodium ferric sulfate contact with a conductive carbon former and controlling its particle size to prepare a sodium ferric sulfate material with excellent electrochemical properties. Summary of the invention

[0006] In view of the deficiencies in the above-mentioned background technology, the present invention provides a porous hollow carbon sphere / sodium iron sulfate composite material and its preparation and application in sodium ion batteries. The method utilizes the capillary adsorption of porous hollow carbon spheres to adsorb the precursor aqueous solution and fill it into the numerous pores inside and on the surface of the porous hollow carbon spheres. After drying, the intermediate of nano-scale particles is tightly anchored inside and on the surface of the porous hollow carbon spheres. After sintering, the intermediate phase changes into an active substance, sodium iron sulfate material. The three-dimensional conductive framework of the porous hollow carbon spheres and the sodium iron sulfate particles form an active network that integrates electron and ion transmission.

[0007] The first object of the present invention is to provide a porous hollow carbon sphere / sodium iron sulfate composite material, the composite material comprising porous hollow carbon spheres and sodium iron sulfate loaded on the porous hollow carbon spheres;

[0008] The sodium iron sulfate loading is 5 to 20 times the mass of the porous carbon spheres.

[0009] Preferably, the diameter of the porous hollow carbon sphere is 150-250 nm, and the porosity is 800-1000 nm. 2 g -1 .

[0010] Preferably, the particle size of the sodium iron sulfate is 10 to 50 nm.

[0011] The second object of the present invention is to provide a method for preparing a porous hollow carbon sphere / sodium iron sulfate composite material, comprising the following steps:

[0012] Evenly dispersing sodium sulfate, ferrous sulfate and a reducing agent in a water solvent in a certain proportion to obtain a precursor solution;

[0013] The precursor solution is mixed with the porous hollow carbon spheres and dried to obtain an intermediate;

[0014] In an inert atmosphere, the intermediate is heated to a predetermined temperature for sintering, and after being kept at the temperature for a period of time, a porous hollow carbon sphere / sodium iron sulfate composite material is obtained.

[0015] Preferably, the molar ratio of the sodium sulfate to the ferrous sulfate is 1:1.0-1.4; the molar ratio of the ferrous sulfate to the reducing agent is 1:0.1-0.5; and the mass fraction of the porous hollow carbon spheres is 1%-15%.

[0016] Preferably, the reducing agent is one or more of ascorbic acid, oxalic acid, glucose, citric acid, sodium oxalate, and sodium citrate.

[0017] Preferably, when the intermediate is heated to a predetermined temperature, the heating rate is 0.5 to 10° C. / min; the predetermined temperature is 300 to 450° C., and the holding time is 8 to 48 hours.

[0018] Preferably, the drying method is evaporative drying, spray drying or freeze drying; the drying temperature is 60 to 180° C., and the drying time is 12 to 24 hours.

[0019] Preferably, the inert atmosphere is argon and / or nitrogen.

[0020] The third object of the present invention is to provide a porous hollow carbon ball / sodium iron sulfate composite material for use in sodium ion batteries.

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] The present invention provides a porous hollow carbon ball / sodium iron sulfate composite material and its preparation and application in sodium ion battery. The raw materials used in the present invention are porous hollow carbon balls, sodium sulfate, ferrous sulfate and reducing agent, and the raw materials are widely available. The preparation method of the present invention does not require dehydration of hydrated ferrous sulfate and the use of various high-cost equipment or drugs. The operation is simple and safe, and the advantages of low cost and high safety of polyanionic sulfate materials are fully continued, which conforms to the green ecological concept of sustainable development. Compared with other carbon composite methods, the method provided by the present invention fully mixes the porous hollow carbon balls with the precursor solution before drying, and stably confines the intermediate substance in the void of the porous hollow carbon balls under the action of capillary adsorption, which reduces the particle size of the active particles and the agglomeration of the particles to the greatest extent, greatly improves the ion and electron transmission capacity between sodium iron sulfate and the carbon matrix, and can bring its electrochemical performance to the best state. The present invention proposes a preparation method for compounding with porous hollow carbon spheres, which does not require the addition of additional hazardous chemicals, is safe and friendly, has a wide range of raw materials, and has a simple preparation process. The prepared porous hollow carbon sphere / sodium iron sulfate composite material has excellent performance and is suitable for commercial large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is a scanning electron microscope microscopic morphology image of the porous hollow carbon sphere / sodium iron sulfate composite material prepared in Example 1.

[0024] Figure 2 This is the XRD pattern of the porous hollow carbon sphere / sodium iron sulfate composite material prepared in Example 1.

[0025] Figure 3 This is the charge and discharge curve of the porous hollow carbon sphere / sodium iron sulfate composite material prepared in Example 1 at a current density of 0.1C.

[0026] Figure 4 This is a graph showing the cycling performance of the porous hollow carbon sphere / sodium iron sulfate composite material prepared in Example 1 at a current density of 0.5C.

[0027] Figure 5 This is a rate performance diagram of the porous hollow carbon sphere / sodium iron sulfate composite material prepared in Example 1 at different current densities of 0.1C to 20C.

[0028] Figure 6 This is a rate performance diagram of the sodium iron sulfate material prepared in Control Example 1 at different current densities of 0.1C to 20C.

[0029] Figure 7 This is a schematic structural diagram of the composite material provided by the present invention. DETAILED DESCRIPTION

[0030] In order to enable those skilled in the art to better understand and implement the technical solution of the present invention, the present invention is further described below in conjunction with specific embodiments and drawings, but the embodiments are not intended to limit the present invention.

[0031] The present invention mainly aims at the problems of low capacity, poor composite effect with conductive carbon, large particle size and various preparation methods of the currently prepared sodium iron sulfate positive electrode material, and the various preparation methods and steps. The method is as follows: adsorption: mixing the precursor aqueous solution with the porous hollow carbon spheres, performing capillary adsorption and then drying; sintering: heating the dried powder to a predetermined temperature under an inert atmosphere for sintering, and obtaining a porous hollow carbon sphere / sodium iron sulfate composite material. The method is simple in process, safe in operation, and the prepared material has excellent electrochemical properties and is suitable for large-scale commercial applications.

[0032] In order to achieve the above-mentioned object, the first aspect of the present invention provides a porous hollow carbon sphere / sodium iron sulfate composite material. Figure 7 As shown, the composite material includes porous hollow carbon spheres and sodium iron sulfate supported on the porous hollow carbon spheres;

[0033] The sodium iron sulfate loading is 5 to 20 times the mass of the porous carbon spheres.

[0034] The porous hollow carbon sphere has a diameter of 150-250 nm and a porosity of 800-1000 nm. 2 g -1 .

[0035] The diameter of the sodium iron sulfate is 10 to 50 nm.

[0036] The composite material provided by the present invention is based on the capillary adsorption of nano-scale sodium ferric sulfate material inside and on the surface of porous hollow carbon spheres, which effectively controls the particle size. The porous hollow carbon spheres provide a stable structural framework, conductive framework and ion channels for sodium ferric sulfate, greatly promoting the transmission of sodium ions and electrons, thereby significantly improving its reversible specific capacity, rate performance and cycle life.

[0037] The second aspect of the present invention provides a method for preparing a porous hollow carbon sphere / sodium iron sulfate composite material, comprising the following steps:

[0038] Evenly dispersing sodium sulfate, ferrous sulfate and a reducing agent in a water solvent in a certain proportion to obtain a precursor solution;

[0039] The precursor solution is mixed with the porous hollow carbon spheres and dried to obtain an intermediate;

[0040] In an inert atmosphere, the intermediate is heated to a predetermined temperature for sintering, and after being kept at the temperature for a period of time, a porous hollow carbon sphere / sodium iron sulfate composite material is obtained.

[0041] The present invention utilizes the capillary adsorption of porous hollow carbon balls to adsorb the precursor aqueous solution into the numerous pores inside and on the surface of the porous hollow carbon balls. After drying, the intermediate of nano-scale particles is tightly anchored inside and on the surface of the porous hollow carbon balls. After sintering, the intermediate is transformed into an active material, sodium iron sulfate material. The three-dimensional conductive framework of the porous hollow carbon balls and the sodium iron sulfate particles form an active network integrating electron and ion transmission.

[0042] The present invention prepares a sodium iron sulfate composite material in contact with a conductive carbon framework-forming body through the capillary adsorption of porous hollow carbon spheres, which can effectively realize the confined anchoring of nanometer-scale sodium iron sulfate particles in the porous hollow carbon spheres, promote the rapid transmission of sodium ions and electrons, and significantly improve its reversible sodium storage capacity, rate performance and cycle life.

[0043] The molar ratio of the sodium sulfate to the ferrous sulfate is 1:1.0-1.4; the molar ratio of the ferrous sulfate to the reducing agent is 1:0.1-0.5; and the mass fraction of the porous hollow carbon spheres is 1%-15%.

[0044] The reducing agent is one or more of ascorbic acid, oxalic acid, glucose, citric acid, sodium oxalate and sodium citrate.

[0045] When the intermediate is heated to a predetermined temperature, the heating rate is 0.5 to 10° C. / min; the predetermined temperature is 300 to 450° C., and the heat preservation time is 8 to 48 hours.

[0046] The drying method is evaporation drying, spray drying or freeze drying; the drying temperature is 60 to 180° C., and the drying time is 12 to 24 hours.

[0047] The inert atmosphere is argon and / or nitrogen.

[0048] The third aspect of the present invention provides an application of a porous hollow carbon sphere / sodium iron sulfate composite material in a sodium ion battery. The porous hollow carbon sphere / sodium iron sulfate composite material provided by the present invention is mainly used as a positive electrode material for a sodium ion battery.

[0049] It should be noted that the experimental methods used in the present invention are all conventional methods unless otherwise specified; the reagents and materials used are all commercially available unless otherwise specified.

[0050] Porous hollow carbon spheres were prepared by the common silica hard template method: 24 mmol tetrapropyl orthosilicate was added to a mixture containing 140 ml ethanol, 20 ml deionized water and 6 ml ammonia water (25 wt%). 1.6 g resorcinol, 2.24 ml formaldehyde (37 wt%) and 2.0 g thiourea were dissolved in the above solution. After stirring for 24 hours, the mixture was rinsed with water and ethanol and dried at 80°C. The resulting product was carbonized at 900°C for 4 hours under atmosphere protection. Finally, it was immersed in hydrofluoric acid (25 wt%) for 24 hours and then filtered with water. Porous hollow carbon spheres were obtained by drying at 80°C.

[0051] Example 1

[0052] A method for preparing a porous hollow carbon sphere / sodium iron sulfate composite material comprises the following steps:

[0053] (1) Dissolve anhydrous sodium sulfate, ferrous sulfate heptahydrate and ascorbic acid in a molar ratio of 1.25:1.4:0.5 in a small amount of deionized water. Add 10% by mass of porous hollow carbon spheres for adsorption. After sufficient adsorption and mixing, place in a 60°C oven and dry for 12 hours. The porous hollow carbon spheres have a diameter of about 200 nm and a porosity of 800 m 2 g -1 .

[0054] (2) The dried intermediate powder was placed in an atmosphere furnace, heated to 350°C at a rate of 5°C / min under an argon atmosphere, kept warm for 12 hours, and then naturally cooled to room temperature to obtain a porous hollow carbon sphere / sodium iron sulfate composite material. The loading amount of sodium iron sulfate in the final prepared electrode was 10 times the mass of the porous carbon sphere.

[0055] Example 2

[0056] A method for preparing a porous hollow carbon sphere / sodium iron sulfate composite material comprises the following steps:

[0057] (1) Dissolve anhydrous sodium sulfate, ferrous sulfate heptahydrate and glucose in a molar ratio of 1.1:1.4:0.4 in a small amount of deionized water. Add 5% by mass of porous hollow carbon spheres for adsorption. After sufficient adsorption and mixing, dry them at 150°C using a spray drying method. The porous hollow carbon spheres have a diameter of about 250 nm and a porosity of 1000 m 2 g -1 .

[0058] (2) The dried intermediate powder was placed in an atmosphere furnace, heated to 380°C at a rate of 10°C / min under an argon atmosphere, kept warm for 10 hours, and then naturally cooled to room temperature to obtain a porous hollow carbon sphere / sodium iron sulfate composite material. The loading amount of sodium iron sulfate in the final prepared electrode was 20 times the mass of the porous carbon sphere.

[0059] Example 3

[0060] A method for preparing a porous hollow carbon sphere / sodium iron sulfate composite material comprises the following steps:

[0061] (1) Dissolve anhydrous sodium sulfate, ferrous sulfate pentahydrate and citric acid in a molar ratio of 1:1.2:0.3 in a small amount of deionized water. Add 15% by mass of porous hollow carbon spheres for adsorption. After sufficient adsorption and mixing, use a freeze-drying device to dry. The porous hollow carbon spheres have a diameter of about 50 nm and a porosity of 950 m 2 g -1 .

[0062] (2) The dried intermediate powder was placed in an atmosphere furnace, heated to 400°C at a rate of 3°C / min in a nitrogen atmosphere, kept at this temperature for 18 hours, and then naturally cooled to room temperature to obtain a porous hollow carbon sphere / sodium iron sulfate composite material. The loading amount of sodium iron sulfate in the final prepared electrode was 6 times the mass of the porous carbon sphere.

[0063] Comparative Example 1

[0064] A method for preparing a sodium iron sulfate material without porous hollow carbon spheres comprises the following steps:

[0065] (1) Dissolve anhydrous sodium sulfate, ferrous sulfate monohydrate and oxalic acid in a molar ratio of 1.3:1.4:0.2 in a small amount of deionized water solution and dry in an oven at 80°C for 24 hours.

[0066] (2) The dried intermediate powder is placed in an atmosphere furnace, heated to 400°C at a rate of 3°C / min under an argon atmosphere, kept warm for 14 hours, and then naturally cooled to room temperature to obtain a sodium iron sulfate material without porous hollow carbon spheres.

[0067] In order to illustrate the relevant properties of the porous hollow carbon sphere / sodium iron sulfate composite material provided by the present invention, it is described in conjunction with the accompanying drawings.

[0068] Figure 1 This is a scanning electron microscope microscopic morphology of the porous hollow carbon sphere / sodium iron sulfate composite material prepared in Example 1. A small portion of the prepared sodium iron sulfate material is adsorbed on the surface of the porous hollow carbon sphere, and most of the sodium iron sulfate material exists in the internal pores of the porous hollow carbon sphere. This body contact structure can provide a fast channel for the transmission of electrons and sodium ions, and combined with the conductive framework of the porous hollow carbon sphere itself, it can effectively improve its various electrochemical properties.

[0069] Figure 2This is the XRD pattern of the porous hollow carbon sphere / sodium ferric sulfate composite material prepared in Example 1. Each characteristic peak can be well matched with the sodium ferric sulfate material, and there is no obvious impurity phase, indicating that the preparation method of the present invention will not destroy the crystal structure of sodium ferric sulfate.

[0070] Combination Figure 1 and Figure 2 According to the analysis, the preparation method of the present invention can well prevent the oxidation of divalent iron in sodium ferric sulfate, because the porous hollow carbon spheres can provide a solid conductive framework and reducing environment for it, and a high-purity sodium ferric sulfate material can be obtained. Most of the sodium ferric sulfate material occupies a large number of pores in the porous hollow carbon spheres, forming a three-dimensional framework with considerable multi-body contacts.

[0071] In order to illustrate the application of the porous hollow carbon sphere / sodium iron sulfate composite material prepared by the present invention in a sodium ion battery, the composite material provided in Example 1 is used as a positive electrode material in a sodium ion battery as an example to carry out sodium ion battery assembly and electrochemical performance testing:

[0072] The battery pole piece was prepared by grinding the porous hollow carbon sphere / sodium iron sulfate composite material prepared in Example 1 with Ketjen black and polyvinylidene fluoride in a mass ratio of 8:1:1 in a mortar with an appropriate amount of N-methylpyrrolidone, and then coating it on aluminum foil, and then drying it in a vacuum drying oven at 120°C for 12 hours, and then cutting it into pole pieces with a diameter of 12 mm. The separator used in the assembled battery was a glass fiber separator, and the electrolyte was 1M NaClO 4 Ester-based electrolyte + 5% FEC, counter electrode is sodium sheet. After standing for 12 hours, constant current charge and discharge tests were carried out at different current densities.

[0073] Figure 3 The first cycle charge and discharge curve of the porous hollow carbon sphere / sodium iron sulfate composite material prepared in Example 1 at a current density of 0.1C. The reversible specific capacity of the porous hollow carbon sphere / sodium iron sulfate composite material is 122.4mAh / g, and the energy density is over 400Wh / kg, which is much higher than similar products. The porous hollow carbon spheres and the sodium iron sulfate material adsorbed inside and on the surface form a good body contact, and the combined framework provides a fast transfer channel for electrons and ions, greatly releasing the electrochemical potential of sodium iron sulfate. It proves the feasibility and effectiveness of the present invention to construct a porous hollow carbon sphere / sodium iron sulfate composite material to improve its electrochemical performance.

[0074] Figure 4The figure is the cycle performance diagram of the porous hollow carbon sphere / sodium iron sulfate composite material prepared in Example 1 at a current density of 0.5C. The capacity retention rate of the porous hollow carbon sphere / sodium iron sulfate composite material in Example 1 is 84.6% after 100 cycles at 0.5C, which has excellent cycle stability. This is because the porous hollow carbon sphere can provide an additional carbon framework to promote particle transmission and play a better supporting role, which can well buffer the volume change during continuous charge and discharge.

[0075] Figure 5 The figure is a rate performance diagram of the porous hollow carbon sphere / sodium iron sulfate composite material prepared in Example 1 at different current densities of 0.1C to 20C. The rate performance of the porous hollow carbon sphere / sodium iron sulfate composite material prepared in Example 1 is also excellent, and it still has a reversible capacity of 65mAh / g at 20C. When the current density is restored to 0.1C, the reversible capacity is 110.4mAh / g, reaching 93.2% of the initial capacity. It proves the excellence of the carbon framework constructed by the present invention and sodium iron sulfate to form a close contact composite material, which greatly improves its electrochemical reaction kinetics.

[0076] Figure 6 The figure is the rate performance diagram of the sodium iron sulfate material prepared in comparative example 1 at different current densities of 0.1C to 20C. Figure 5 In contrast to the porous hollow carbon sphere / sodium iron sulfate composite material of Example 1, the sample of the control example has a reversible capacity of 92 mAh / g at 0.1C, and then its capacity decays rapidly with the increase of current density, and has almost no discharge capacity at 20C. The comparison results show that the sodium storage performance of the porous hollow carbon sphere / sodium iron sulfate composite material in the present invention is greatly improved compared with the sodium iron sulfate material itself.

[0077] The present invention describes preferred embodiments and their effects. However, those skilled in the art may make additional changes and modifications to these embodiments once they are aware of the basic creative concept. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.

[0078] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A porous hollow carbon sphere / sodium iron sulfate composite material, characterized in that: The composite material comprises porous hollow carbon spheres and sodium iron sulfate supported on the porous hollow carbon spheres; The sodium iron sulfate loading is 5 to 20 times the mass of the porous carbon spheres.

2. The porous hollow carbon sphere / sodium iron sulfate composite material according to claim 1, characterized in that: The porous hollow carbon sphere has a diameter of 150-250 nm and a porosity of 800-1000 nm. 2 g -1 .

3. The porous hollow carbon sphere / sodium iron sulfate composite material according to claim 1, characterized in that: The particle size of the sodium ferric sulfate is 10 to 50 nm.

4. A method for preparing the porous hollow carbon sphere / sodium iron sulfate composite material according to any one of claims 1 to 3, characterized in that: The following steps are involved: Evenly dispersing sodium sulfate, ferrous sulfate and a reducing agent in a water solvent in a certain proportion to obtain a precursor solution; The precursor solution is mixed with the porous hollow carbon spheres and dried to obtain an intermediate; In an inert atmosphere, the intermediate is heated to a predetermined temperature for sintering, and after being kept at the temperature for a period of time, a porous hollow carbon sphere / sodium iron sulfate composite material is obtained.

5. The method for preparing the porous hollow carbon sphere / sodium iron sulfate composite material according to claim 4, characterized in that: The molar ratio of the sodium sulfate to the ferrous sulfate is 1:1.0-1.4; the molar ratio of the ferrous sulfate to the reducing agent is 1:0.1-0.5; and the mass fraction of the porous hollow carbon spheres is 1%-15%.

6. The method for preparing the porous hollow carbon sphere / sodium iron sulfate composite material according to claim 4, characterized in that: The reducing agent is one or more of ascorbic acid, oxalic acid, glucose, citric acid, sodium oxalate and sodium citrate.

7. The method for preparing the porous hollow carbon sphere / sodium iron sulfate composite material according to claim 4, characterized in that: When the intermediate is heated to a predetermined temperature, the heating rate is 0.5 to 10° C. / min; the predetermined temperature is 300 to 450° C., and the heat preservation time is 8 to 48 hours.

8. The method for preparing the porous hollow carbon sphere / sodium iron sulfate composite material according to claim 4, characterized in that: The drying method is evaporation drying, spray drying or freeze drying; the drying temperature is 60 to 180° C., and the drying time is 12 to 24 hours.

9. The method for preparing the porous hollow carbon sphere / sodium iron sulfate composite material according to claim 4, characterized in that: The inert atmosphere is argon and / or nitrogen.

10. Use of the porous hollow carbon sphere / sodium iron sulfate composite material according to any one of claims 1 to 3 in a sodium ion battery.

Citation Information

Patent Citations

  • A composite electrode material of porous hollow carbon spheres loaded with tin sulfide nano quantum dots

    CN108987735A

  • Carbon-coated sodium ferric sulfate positive electrode material and preparation method thereof

    CN115020681A

  • Sodium ferrous sulfate / carbon nanotube composite positive electrode material, preparation method and sodium ion battery

    CN115172724A

  • Method for preparing carbon-coated sodium ferric sulfate material, carbon-coated sodium ferric sulfate material and battery

    CN116230888A

  • Composite sodium ferric phosphate material packaged by hollow mesoporous carbon spheres and preparation method and application thereof

    CN116605869A

Cited By

  • Positive electrode active material and preparation method thereof, positive electrode plate and energy storage device

    CN117832446A